Implementasi Kurikulum Merdeka Belajar Pada Mata Kuliah PAI di Universitas Sumatera Utara - Azhari, Suci Putriani; Achadi, Muh.Wasith (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2023)
The puspose of this research is to analyze the implementation of the independent curriculum in PAI courses at public universities. The method used in this research is descriptive qualitative. The research object chosen was a lecturer who teaches PAI courses at the University of North Sumatra. Data collection in this research used observation, interviews and documentation, namely analyzing the RPS. The results of this research indicate that the implementation of the independent curriculum in PAI courses has been implemented. Considering that PAI material is included in the MKWK section, the learning uses a project-based learning model approach. The obstacles faced in PAI learning are limited time, diverse understanding, complex material, and performance evaluation. Each obstacle encountered certainly has a solution so that learning continues according to the expected goals